2002
DOI: 10.1038/sj.onc.1205690
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin H/cdk7/Mat1 kinase activity is regulated by CK2 phosphorylation of cyclin H

Abstract: Cyclin dependent kinases are regulated by phosphorylation and dephosphorylation of the catalytic cdk subunits, by assembly with specific cyclins and by specific inhibitor molecules. Recently, it turned out that cyclins are also phosphoproteins, which means that they are also potential targets for a regulation by phosphorylation and dephosphorylation. Here, we show that cyclin H was phosphorylated by protein kinase CK2. Like most other CK2 substrates cyclin H was much better phosphorylated by the CK2 holoenzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Similar to RNSP1, here we showed that an inhibition of the hPrp3p phosphorylation also leads to an inhibition of the splicing. Several proteins, which are implicated in transcription and posttranscriptional processes are substrates for protein kinase CK2 including RNA polymerase II (Payne et al, 1989), cyclin H (Schneider et al, 2002) and FCP1 (TFIIF-dependent CTD phosphatase) (Trembley et al, 2003). Interestingly, RNPS1 also interacts with the largest subunit of RNA polymerase II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to RNSP1, here we showed that an inhibition of the hPrp3p phosphorylation also leads to an inhibition of the splicing. Several proteins, which are implicated in transcription and posttranscriptional processes are substrates for protein kinase CK2 including RNA polymerase II (Payne et al, 1989), cyclin H (Schneider et al, 2002) and FCP1 (TFIIF-dependent CTD phosphatase) (Trembley et al, 2003). Interestingly, RNPS1 also interacts with the largest subunit of RNA polymerase II.…”
Section: Discussionmentioning
confidence: 99%
“…Among the more than 300 substrates discovered to this date, are a lot of proteins that are implicated in cell cycle control, DNA replication/repair, proliferation and transcription/translation (Meggio and Pinna, 2003). The C-terminal domain (CTD) of the largest RNA polymerase II subunit (Cabrejos et al, 2004), the TFIIF-dependent CTD phosphatase 1 (FCP1) (Palancade et al, 2002) and cyclin H (Faust et al, 2002;Schneider et al, 2002;Krempler et al, 2005) belong to the substrates that are known to regulate transcriptional events. Cyclin H is phosphorylated at threonine 315 by CK2 and this phosphorylation is needed for full activity of the cdk7/ cyclin H/Mat1 complex towards a CTD peptide of RNA polymerase II.…”
Section: Introductionmentioning
confidence: 99%
“…Today, CK2 is known to phosphorylate more than 300 cellular and viral proteins, and yet the list is far from complete, as shown by comparative amino acid sequence screen analyses among putative CK2 phosphorylation motifs/sites (36,53). Among these substrates are proteins involved in DNA replication (topoisomerase I [36,44]), transcription (c-Myc [36,44]), cell cycle control (cyclin H [55]), ribosome biogenesis (L5 [42]), apoptosis induction (Bid [14]), and cell differentiation (HOXB7 [71]), as well as numerous viral proteins (e.g., EB2 from Epstein-Barr virus [[EBV] [35], EBNA-2 from EBV [24], NS2 from hepatitis C virus [HCV] [21], and ZEBRA from EBV [17]), that comprise ca. 10% of the known CK2 substrates (36).…”
mentioning
confidence: 99%
“…Several of the nuclear CK2 substrates are proteins that are known to regulate transcriptional events, including the CTD of the largest RNAP II subunit, cyclin H, and FCP1 (TFIIF-dependent CTD phosphatase 1) (36,45). CK2 phosphorylation of cyclin H is important for full cyclin H/CDK7/ Mat1 kinase activity with a CTD peptide as a substrate (42). In Xenopus laevis cell extracts, CK2 phosphorylation also enhances the phosphatase activity of FCP1 and binding to the RAP74 subunit of TFIIF, thereby promoting sequential transcriptional cycles (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we show here that serine residue 53 (Ser-53) of RNPS1 is phosphorylated by casein kinase II (CK2). CK2 phosphorylates several key cell cycle and transcriptional proteins (36,42), interacts with multiple signaling pathways, and is proposed to be an important mediator of cell survival. In contrast to the effect of SR protein kinases on SR proteins, we show that the nuclear localization of RNPS1 is not affected by CK2 phosphorylation.…”
mentioning
confidence: 99%